2020
DOI: 10.1109/access.2020.2973930
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Look-Up-Tables Based Behavioral Model for Dynamic Nonlinear Power Amplifiers

Abstract: A new look-up table based behavioral model for dynamic nonlinear power amplifiers is proposed. This model labelled as hybrid look-up tables model is based on the combination of a memoryless look-up table sub-model and a nested look-up tables one. It is demonstrated that the proposed model circumvents the computational complexity associated with the parameters identification in analytically defined behavioral models. Moreover, the proposed model reduces the size of the standalone nested look-up tables model by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, their memory-less nature forbids its implementation towards the dynamical realistic MIMO PAs driven by a digital baseband processing module. For this purpose, Dalbah et al [95] have taken the impact of MEs for dynamic nonlinear systems in the bandwidth range of 100 MHz by deploying a typical memory-less LUT with a hybrid LUT-based model referred to as nested LUT sub-model. Since the MIMO beam scanning constitutes an impulsive coefficient learning of high data rates and beamforming algorithms, and as a result, the bottlenecks of computational intensiveness hinder the iterative runtime of dense memory depth orders [85], [96].…”
Section: Representation Of Machine Learning Based Behavioral Modelsmentioning
confidence: 99%
“…However, their memory-less nature forbids its implementation towards the dynamical realistic MIMO PAs driven by a digital baseband processing module. For this purpose, Dalbah et al [95] have taken the impact of MEs for dynamic nonlinear systems in the bandwidth range of 100 MHz by deploying a typical memory-less LUT with a hybrid LUT-based model referred to as nested LUT sub-model. Since the MIMO beam scanning constitutes an impulsive coefficient learning of high data rates and beamforming algorithms, and as a result, the bottlenecks of computational intensiveness hinder the iterative runtime of dense memory depth orders [85], [96].…”
Section: Representation Of Machine Learning Based Behavioral Modelsmentioning
confidence: 99%
“…This paper uses the power series model as the nonlinear mathematical model of the power amplifier. In the literature (Dalbah et al , 2020; Wang et al , 2019c; Pérez-Hernández et al , 2021), the baseband equivalent input and output relationship are shown in equation (1): where i denotes the i-th wireless communication transmit link. To make a clarification here, the power amplifier because it is at the transmitting end of the subsystem, i can denote both the i-th subsystem and the transmitting link of the i - th subsystem.…”
Section: Establish-related Mathematical Modelsmentioning
confidence: 99%
“…This paper uses the power series model as the nonlinear mathematical model of the power amplifier. In the literature (Dalbah et al, 2020;Wang et al, 2019c;Pérez-Hern andez et al, 2021), the baseband equivalent input and output relationship are shown in equation ( 1):…”
Section: Establish-related Mathematical Modelsmentioning
confidence: 99%
“…This model compensates for static distortions but has limited performance in the presence of strong memory effects. Other models that can be considered as suitable candidates for RF digital predistortion are the nested look-up tables based predistorters [23]- [24]. However, these typically require extensive processing to synthesize the nested LUT which usually has a very large size.…”
Section: A Proposed Predistortion Functionmentioning
confidence: 99%